EVALUATION RESULTS OF NUSANTARA 5 AUTONOMOUS UNDERWATER VEHICLE (N5-AUV) IN A CONTROLLED ENVIRONMENT AND THE OPEN SEA: HASIL EVALUASI NUSANTARA 5 AUTONOMOUS UNDERWATER VEHICLE (N5-AUV) DI LINGKUNGAN TERKONTROL DAN LAUT TERBUKA - Muhammad Rafly Amanullah Fahmi; Indra Jaya; Muhammad Iqbal (Jurnal Teknologi Perikanan dan Kelautan, 2025)
An Autonomous Underwater Vehicle (AUV) is a vehicle operated underwater using a propulsion system, controlled and navigated by a computer system, and capable of maneuvering in three dimensions. It is designed to perform tasks underwater that are difficult for humans to accomplish. This research aims to document the design and development of the Nusantara 5 AUV made by the MITR Club of Marine Science and Technology, Faculty of Fisheries and Marine Sciences, IPB University, as well as to evaluate its performance both in field conditions and controlled environments. The evaluation method for the vehicle involved comparing the movement results in water with the programmed motions of straight movement, turning, and gliding. The performance testing results indicated that the AUV could move straight with an average error of 2.8° in a controlled environment, while in the sea, the average error reached 5.4° because the AUV was tossed around by the sea waves. During turning maneuvers in controlled conditions, the AUV required 12.8 seconds to adjust its path after turning, whereas in the sea, it took 20 seconds. Gliding motion was still not perfect, both in the test pool and in the sea, as it tended to move up and down. This indicated a weakness in the Nusantara 5 AUV itself. However, the advantage of the Nusantara 5 AUV itself was in its smaller size compared to its predecessors and the use of fewer thrusters, thus minimizing manufacturing costs.